Acute mammary and liver transcriptome responses after an intramammary Escherichia coli lipopolysaccharide challenge in postpartal dairy cows. Issue 4 (28th April 2015) - Minuti, Andrea; Zhou, Zheng; Graugnard, Daniel E.; Rodriguez‐Zas, Sandra L.; Palladino, Alejandro R.; Cardoso, Felipe C.; Trevisi, Erminio; Loor, Juan J.
Abstract The study investigated the effect of an intramammary lipopolysaccharide (LPS) challenge on the bovine mammary and liver transcriptome and its consequences on metabolic biomarkers and liver tissue composition. At 7 days of lactation, 7 cows served as controls (CTR) and 7 cows (LPS) received an intramammary Escherichia coli LPS challenge. The mammary and liver tissues for transcriptomic profiling were biopsied at 2.5 h from challenge. Liver composition was evaluated at 2.5 h and 7 days after challenge, and blood biomarkers were analyzed at 2, 3, 7 and 14 days from challenge. In mammary tissue, the LPS challenge resulted in 189 differentially expressed genes (DEG), with 20 down‐regulated and 169 up‐regulated. In liver tissue, there were 107 DEG in LPS compared with CTR with 42 down‐regulated and 65 up‐regulated. In mammary, bioinformatics analysis highlighted that LPS led to activation of NOD‐like receptor signaling, Toll‐like receptor signaling, RIG‐I‐like receptor signaling and apoptosis pathways. In liver, LPS resulted in an overall inhibition of fatty acid elongation in mitochondria and activation of the p53 signaling pathway. The LPS challenge induced changes in liver lipid composition, a systemic inflammation (rise of blood ceruloplasmin and bilirubin), and an increase in body fat mobilization. The data suggest that cells within the inflamed mammary gland respond by activating mechanisms of pathogen recognition. However, in the liver the response likely depends on mediators originating from the udder that affect liver functionality and specifically fatty acid metabolism (β‐oxidation, ketogenesis, and lipoprotein synthesis).